EVALUATION OF TEACHER ASSESSMENT CAPABILITIES THROUGH MULTI-STAGE ADAPTIVE TESTING - Habib, Syarifah Eva Surya (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2023)
The objective of this study is to assess MSAT (MULTI-STAGE ADAPTIVE TEST) performance of 21 Teachers and was carried out at Madrasah Ibtidaiyah Negeri 9 Nagan Raya, with the research subjects being Madrasah teachers and performed with three cycle tests. In accordance with the assessment results, the average score increased from pre-cycle to cycle I to cycle II, where the pre-cycle observation average score only reached 6.4 while in cycle I it reached 11.4, indicating that the teacher's ability to the assessment process using the multi-stage adaptive testing (MSAT) application is good. Cycle II then received a score of 15.8, indicating that the teacher's proficiency in the assessment process utilizing the multi-stage adaptive testing (MSAT) application was excellent.